Self-induced optical non-reciprocity - Zhu-Bo Wang; Yan-Lei Zhang; Xin-Xin Hu; Guang-Jie Chen; Ming Li; Peng-Fei Yang; Xu-Bo Zou; Peng-Fei Zhang; Chun-Hua Dong; Gang Li; Tian-Cai Zhang; Guang-Can Guo; et al. (Light: Science & Applications)
Abstract Non-reciprocal optical components are indispensable in optical applications, and their realization without any magnetic field has attracted increasing research interest in photonics. Exciting experimental progress has been achieved by either introducing spatial-temporal modulation of the optical medium or combining Kerr-type optical nonlinearity with spatial asymmetry in photonic structures. However, extra driving fields are required for the first approach, while the isolation of noise and the transmission of the signal cannot be simultaneously achieved for the other approach. Here, we propose the mechanism of nonlinear non-reciprocal susceptibility for optical media and experimentally realize the self-induced isolation of optical signals without any external bias field. The self-induced isolation by the input signal is demonstrated with an extremely high isolation ratio of 63.4 dB, a bandwidth of 2.1 GHz for 60 dB isolation, and a low insertion loss of ~1 dB. Furthermore, the new mechanism allows novel functional optical devices, including polarization purification and non-reciprocal leverage. A complete passive isolator is realized by introducing an asymmetry cavity. It is demonstrated that the 70 μW signal could lever the non-reciprocity and realize a 30 dB isolation of the backward laser with a power 100 times higher. The demonstrated nonlinear non-reciprocal medium provides a versatile tool to control light and deepen our understanding of light-matter interactions and enables applications ranging from topological photonics to unidirectional quantum information transfer in a network.